2018
DOI: 10.1016/j.jss.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a GitHub Star? Understanding Repository Starring Practices in a Social Coding Platform

Abstract: Besides a git-based version control system, GitHub integrates several social coding features. Particularly, GitHub users can star a repository, presumably to manifest interest or satisfaction with an open source project. However, the real and practical meaning of starring a project was never the subject of an in-depth and well-founded empirical investigation. Therefore, we provide in this paper a throughout study on the meaning, characteristics, and dynamic growth of GitHub stars. First, by surveying 791 devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 218 publications
(111 citation statements)
references
References 55 publications
0
97
0
2
Order By: Relevance
“…The above phenomena may impact reproducibility of research studies if the population of software libraries under analysis is retrieved using a single metric of popularity (e.g., [7] analysed the top 5,000 GitHub projects based on their number of stars). Other popularity metrics may lead to different research findings, limiting the generalisability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The above phenomena may impact reproducibility of research studies if the population of software libraries under analysis is retrieved using a single metric of popularity (e.g., [7] analysed the top 5,000 GitHub projects based on their number of stars). Other popularity metrics may lead to different research findings, limiting the generalisability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…breaking up exclusionary structures) [26:299]. In this framing of openness, Schlagwien et al [26] WikiTribune shares characteristics with other production communities like GitHub (a digital workspace for the production of software and nonsoftware digital artifacts [5,24]) and Wikipedia (a non-profit wiki-based global encyclopedia), however, the way in which the various open principles manifest and are enacted differ across projects. We consider WikiTribune a "hybrid" model because it is a for-profit organization that hires and manages paid professionals to produce content (unlike GitHub and Wikipedia), but also opens up the production of its product to anyone that wants to join and the consumption of its product to anyone that visits the website (unlike more traditional organizations [9]), open source development (e.g.…”
Section: Characterizing Wikitribune's Modelmentioning
confidence: 99%
“…Also, some researchers investigated other features and tools of GitHub, eg, forking, starring, watching, and Gists . Specifically, Jiang et al explored the forking in GitHub and found that forking is mainly used for making contributions of original repositories, and it is beneficial for OSS community.…”
Section: Preliminariesmentioning
confidence: 99%
“…Specifically, Jiang et al explored the forking in GitHub and found that forking is mainly used for making contributions of original repositories, and it is beneficial for OSS community. Borges et al presented a thorough study on the GitHub stars. They conducted an analysis on the top‐5000 most starred GitHub repositories and proposed four patterns to describe stars growth.…”
Section: Preliminariesmentioning
confidence: 99%